2021
DOI: 10.52965/001c.27579
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hopelessness And Suicidal Ideation In Iranian Medical Students: A Cross-Sectional Study

Abstract: Background and ObjectivesThere are limited studies regarding suicidal ideation among Iranian medical students. We aimed to evaluate the prevalence of suicidal ideation and its association with hopelessness among Tehran University of Medical Sciences (TUMS) medical students. MethodsWe designed a cross-sectional study conducted in TUMS in 2018. We developed a questionnaire consisting of three parts; the Beck Hopelessness Scale (BHS), four questions regarding suicidal ideation, and questions regarding demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
4
1
1
Order By: Relevance
“…It is well established that hopelessness is one of the strongest predictors of suicide, especially when accompanied by depression (Wolfe et al, 2019). Numerous studies have found that hopelessness is positively associated with suicidal ideation among different populations, such as adolescents (Wolfe et al, 2019), general university students (Chang, 2017), and medical students (Sadeghian et al, 2021;Tin et al, 2015). Moreover, a previous study has demonstrated that hopelessness is linked with suicidal intent and suicidal attempts (Klonsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that hopelessness is one of the strongest predictors of suicide, especially when accompanied by depression (Wolfe et al, 2019). Numerous studies have found that hopelessness is positively associated with suicidal ideation among different populations, such as adolescents (Wolfe et al, 2019), general university students (Chang, 2017), and medical students (Sadeghian et al, 2021;Tin et al, 2015). Moreover, a previous study has demonstrated that hopelessness is linked with suicidal intent and suicidal attempts (Klonsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Items with unfavorable statements (items 2, 5, 6, 8, 9) were scored as follows: 4 (strongly disagree), 3 (disagree), 2 (agree), 1 (strongly agree) (García et al, 2019). The RSES has a total score between 10-40, based on which, self-esteem can be categorized into 3 levels: low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (26)(27)(28)(29), and high (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) self-esteem (García et al, 2019). The Indonesian version of the RSES has been validated in a previous study and has high internal reliability -as indicated by Cronbach's α = 0.875 (Kaloeti and Ardhiani, 2020).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Обследуемые пациенты были разделены на две группы в зависимости от выявленного уровня безнадежности: 1-я группа -пациенты с отсутствием чувства безнадежности и низким уровнем безнадежности (n=89; 76,7%), 2-я группа -со средним и высоким уровнями безнадежности (n=27 -23,3%). Данное разделение обусловлено тем, что суицидальная идеация чаще встречается у лиц со средним и высоким уровнями безнадежности, чем у лиц без выявленной безнадежности или с низким уровнем безнадежности [20].…”
Section: материалы и методыunclassified
“…These researchers 9 reported that people who had attempted suicide in the year prior to the study had higher scores for hopelessness than those with a prior history of suicide attempts. A cross-sectional study assessing hopelessness and suicidal ideation among Iranian medical students 6 found that after adjusting for demographic variables (e.g., age, gender, and marital status), hopelessness was independently associated with suicidal ideation. A meta-analysis of longitudinal studies 10 investigating depression and hopelessness as predictors of suicidal ideation, attempts, and completion concluded that hopelessness was the strongest predictor of each of these factors.…”
Section: Introductionmentioning
confidence: 99%